Influence of redox electrolyte on the device performance of phenothiazine based dye sensitized solar cells. (2nd May 2018) - El-Shishtawy, Reda M.; Decoppet, Jean-David; Al-Zahrani, Fatimah A. M.; Cao, Yiming; Khan, Sher B.; Al-Ghamdi, Mohammed S.; Alhogbi, Basma G.; Asiri, Abdullah M.; Zakeeruddin, Shaik M.; Grätzel, Michael
Abstract : We report on a new organic dye based on phenothiazine for DSC application. Abstract : We designed and synthesized a metal-free organic sensitizer based on phenothiazine as the core moiety for application in dye-sensitized solar cells (DSCs). The structure of the donor–π–bridge–acceptor (D–π–A) dye 3-(5-(7-(( E )-3, 4, 5-trimethoxystyryl)-10-octyl-10 H -phenothiazin-3-yl)thiophen-2-yl)-2-cyanoacrylic acid (TMPTZT ) has tri-methoxy phenyl as a donor segment on a phenothiazine core and cyanoacrylic acid as an acceptor group. In this study, we investigated the influence of iodide/triiodide and Co(bpy)3 2+/3+ complexes as redox electrolytes on the DSC device performance. The maximal monochromatic incident photon to current conversion efficiency (IPCE) reached a value of 70%. The solar light to electrical energy conversion efficiency of the devices with a volatile solvent based iodide/triiodide electrolyte reached up to 5.1% at AM 1.5G illumination, whereas the devices with Co(bpy)3 2+/3+ and ionic liquid electrolytes showed efficiencies of 4.9% and 4.5%, respectively. The DSC devices were characterized using charge extraction and V oc decay techniques to understand the difference in the photovoltaic performance of this metal free organic dye with these three types of redox electrolytes.